IMPLEMENTASI BUDIDAYA IKAN DAN SAYUR RAMAH LINGKUNGAN DI PONDOK PESANTREN DESA BANDARKIDUL, KEDIRI - Alba, Cecep; Hidayat, Esa Fajar; Masriah, Andi; Nadiro, Vina Nur; Pratiwi, Rizky Kusma; Hadiana, Hadiana (Universitas Mataram, 2025)
A common problem encountered in densely populated residential areas is waste accumulation. The majority of this waste consists of organic and inorganic household refuse. While organic waste is polluting, it is biodegradable and decomposes relatively quickly. In contrast, inorganic waste—particularly plastics—requires an extensive period to decompose in the natural environment. Consequently, this community service program aims to recycle plastic waste so that it can be reused and even acquire economic value. The plastic material utilized is discarded single-use water gallon containers, which often accumulate and hold little to no resale value. The target participants of this program are the students (santri) of Pondok Pesantren Al-Ishlah in Bandarkidul Village, Kediri City. The method employed involves providing education and hands-on training in cultivating catfish (Clarias sp.) and water spinach (Ipomoea aquatica) within a single reused gallon container which is known as Budikdamlon (aquaculture using gallon). The training also covers maintenance practices up to the harvest stage. As members of the younger generation, it is expected that the trained students will serve as agents of change—youth who not only possess intellectual capacity but also actively implement their knowledge in alignment with religious values.